Impacto da satisfação de puérperas com o parto vaginal na autoeficácia para amamentar - Campos, Fernanda Câmara (2015)
The aim of this study was to verify the criteria va lidity of the subscales 2 and 3 of Questionnaire of Experience and Satisfaction with t he Childbirth (QESP), considering the Breastfeeding Self-efficacy Scale Short Form (BSES- SF) as the gold standard. It was a methodological study, which aims to evaluate the cr iteria validity of the sub-scales 2 and 3 of QESP, using the gold standard to BSES- SF, performe d at the Teaching Maternity Assis Chateaubrian in Fortaleza. The sample was consisted of 237 mothers. Data collection occurred in the period from July to October 2014, f rom the steps: in puerperal rooming-in, application of identification form that contained s ociodemographic characteristics and obstetric and postpartum women, then application of the subscales 2 and 3 of Questionnaire of Experience and Satisfaction with the Childbirth (QESP) and Breastfeeding Self-Efficacy and Scale- Short Form (BSES-SF). The research was a pproved by the Research Ethics Committee of the Teaching Maternity Assis Chateaubr iand. It was used SPSS version 20.0 for data analysis. The women in the study had a mean ag e of 22.4 years, most were between 20 and 35 years (56,5%), came from the capital (75,9%) , were not white (78,9% ), were married/ common-law marriage (77,6%), with a family income o f up to 1 MW (47,3%) and were between 9 and 12 years of study (67,5%). It was obs erved that most of the women had had six or more prenatal appointments (66.2%), had two or m ore pregnancies (50,6%), was primiparous (52,8%), for multiparous, most had prev ious vaginal birth (85,7%), no abortion (86,1%), breastfed before (87,5%); kept immediate t ouch with newborn (64,1%) and had a companion of their choice in the delivery room (66, 2%). The correlation between the scores of QESP and sociodemographic and obstetric variable s showed statistically significant correlation, age (p = 0.018), marital status (p = 0 .027) and the presence of a partner in the delivery room (p = 0.015). Correlations between sco res of BSES-SF and the sociodemographic and obstetric variables presented as statistically significant: the marital status (p = 0.001), conducting abortion before (p = 0.044), breastfeeding practice before (p = 0.008) and guidance on breastfeeding during prenata l care (p = 0, 021). Cronbach's Alpha the subscales 2 and 3 of QESP in the study population w as 0,909 e 0,828, respectively, proved to be a valid instrument. There was a significant corr elation between the scores and the scores of QESP BSES-SF (p = 0,013). Therefore, it is conclude d that, among women who experienced vaginal delivery, high self-efficacy in breastfeedi ng was associated with greater overall satisfaction of mothers with the experience of chil dbirth. There is, therefore, the importance of ensuring women actions that promote their satisf action during the birth process, as well as their confidence in the act of breastfeeding, by pr omoting breastfeeding.